A Conceptual Framework to Build Brand Loyalty in the Modern Marketing Environment - Latif, Wasib B; Islam, Md. Aminul; Noor, Idris Bin Mohd (Journal of Asian Scientific Research, 2014)
Building brand loyalty in a competitive market can play an efficient role in the modern marketing environment. It is now widely acknowledged by companies and business enterprises that strong brand loyalty will make a competitive advantage in the marketplace that will increase their overall knowledge with experiences and trustworthiness. Indeed, recent trends in modern marketing have changed tremendously, and study of brand loyalty is increasingly becoming essential to keep pace with this change. In this conceptual paper, we have summarized the literatures on currently prevailing concepts and approaches on brands that will allow us to identify the necessary components of brand loyalty, and therefore will help companies and business enterprises to improve their marketing efficiency. Based on a comprehensive review of several earlier works, here we propose a plausible framework for building brand loyalty in sequential order, namely, familiarity of the brand, satisfaction of customer of the brand, trust on the brand and attitudinal loyalty of the brand. In this review, we put forward the perception that brand loyalty-building challenge need to be connected with organizational processes which will support to bring the promises as well as commitments to the customers through organizational aggregate activities. We suggest that these aggregate activities could play an imperative role in building brand loyalty among customers. As a whole, based on the existing literatures, we have tried to provide a comprehensive view on the essential components of brand loyalty for building brand loyalty in a competitive market.